DENIAL OF INFORMATION TO THE OFFICER OF THE COMMUNAL MILITIA, POLICE AND SECURITY SERVICES: BETWEEN PUNISHMENT AND NON PUNISHMENT - Milosavljević, Bogoljub (Pravni zapisi, 2022)
The paper is dealing with authorities of the comunal militie, police and security services to collect information from citizens and legal persons. While the authorities of police and security services are based on willingness of givinginformation, at the same time the authorities of communal militie are based on obligingness of giving information. The person who does not provide requested information to communal policeman is warned by fine, which is unconditional (there is no legal reason for denial of information). The very request for giving information is exlusively based on resonable presumption of the communal policeman which is based on his discretionary power. In this paper the author also points out to certain lack of solutions in the legal provisions of the Law on Police which determine the authorities of the police to collect information, as well the authorities to invite persons for police interview in order to request information which is differently set up in regard to the Law on Criminal Procedure. In the conclusion it is emphasised that regulations of the Law on Communal Militie and the Law on Police give broader discretionary power to police officers what is not in accordance with the rule of law. Also, the punishment for denial of giving information to communal militie is not in accordance with the Constitution and with fundamental human rights, as well analised examples show the obvious weakness of legal process and consitutional control of law.